Using Slack and AWS EventBridge to Automate Your DevOps Tasks. - Rivas, Carlos (linkedin.com, 2020)
Learn how to use EventBridge to integrate third-party apps, such as Slack, with AWS for better communication, collaboration, and even automation of DevOps tasks.